1982
DOI: 10.1080/07481188208252117
|View full text |Cite
|
Sign up to set email alerts
|

Death anxiety among nursing home residents: A comparison of the young-old and the old-old

Abstract: The purpose of this research was (a) to determine whether there is a comparative difference in the level of conscious death anxiety between young-old and the old-old nursing home residents and (b) to assess the predictive value of educational attainment, gender, subjective health, functional ability, social support, and length of stay on the conscious death anxiety of the persons in the two age groups. A discriminant analysis of 228 residents from three nursing homes revealed that among the 103 young-old subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Previous studies show that loneliness is very common among older adults and that it increases the risk of mortality (Steptoe, Shankar, Demakakos, & Wardle, ; Tilvis, Laitala, Routasalo, & Pitkälä, ). Research has determined that older adults who live in city centres (Erol, Sezer, Şişman, & Öztürk, ), are of advanced age (Bilgili et al., ; Dykstra, van Tilburg, & de Jong Gierveld, ; Softa, Öztürk, Dindaş, & Göçmen, ), live alone in their own houses (Kılıç, Karadağ, & Koçak, ), live in institutions (Bilgili et al., ), over longer terms (Mullins & Lopez, ) and have no income (Khorshid et al., ; Mullins & Lopez, ) experience more loneliness. Loneliness was also found to have negative effects on life satisfaction in older adults (Kapıkıran, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that loneliness is very common among older adults and that it increases the risk of mortality (Steptoe, Shankar, Demakakos, & Wardle, ; Tilvis, Laitala, Routasalo, & Pitkälä, ). Research has determined that older adults who live in city centres (Erol, Sezer, Şişman, & Öztürk, ), are of advanced age (Bilgili et al., ; Dykstra, van Tilburg, & de Jong Gierveld, ; Softa, Öztürk, Dindaş, & Göçmen, ), live alone in their own houses (Kılıç, Karadağ, & Koçak, ), live in institutions (Bilgili et al., ), over longer terms (Mullins & Lopez, ) and have no income (Khorshid et al., ; Mullins & Lopez, ) experience more loneliness. Loneliness was also found to have negative effects on life satisfaction in older adults (Kapıkıran, ).…”
Section: Introductionmentioning
confidence: 99%
“…Further, death anxiety has a significant impact on the lives of older adults (Öztürk, Karakuş, & Tamam, ). Although anxiety about death has been shown to increase with age (Depaola, Griffin, Young, & Neimeyer, ; Mullins & Lopez, ), some studies found that anxiety about death decreased and remained unchanged after a certain period in older adults (Depaola et al., ; Russac, Gatliff, Reece, & Spottswood, ). Nonetheless, a large proportion of studies have shown that anxiety about death increases with age (Galt & Hayslip, ; Suhail & Akram, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although the literature is somewhat inconsistent in regard to fear of death in older adults, there is reasonable evidence for its existence among older adults (Cicirelli, 2002;Mullins & Lopez, 1982;Neimeyer & Moore, 1994;Viney, 1984). Some theorists (e.g., Carstensen, 1995, Erikson, 1982McCoy, Pyszczynski, Solomon, & Greenberg, 2000;Wong, 2000) argue that as nearness to death increases and existing anxiety-buffering systems deteriorate (implying an emergence of fear of death), then coping strategies are utilized to adapt to the last stage of life and reach an acceptance of death.…”
mentioning
confidence: 98%
“…Cheok et al (1996);Drageset et al (2013a);Moreno et al (2008Moreno et al ( -2009Mullins and Lopez (1982);Neville and Teri (2011);Parmelee et al (1993); Smalbrugge et al (2005a); Smalbrugge et al (2005b); Thomasma et al (2013); Drageset et al (2013b); Junginger et al (1993); Moreno et al (2008-2009); Mullins and Lopez (1982); Smalbrugge et al (2005a); Smalbrugge et al (2013); Cheok et al (1996); Drageset et al (2013b); Milliren (1977); Moreno et al (2008-2009); Mullins and Lopez (1982); Neville and Teri (2011); Parmelee et al (1993); Smalbrugge et al (2005a); Smalbrugge et al (2005b) Zuidema et al (2013); Drageset et al (2013b); Junginger et al (1993); Smalbrugge et al (2005a); Smalbrugge et al (2005b) 0 0/5 (0%) Children (yes/no) Smalbrugge et al (2005a); Smalbrugge et al (2005b) 0 0/2 (0%) a…”
mentioning
confidence: 99%